The effects of holistic, external, and internal attentional focus instructions on power and kinematics of the hang power snatch in highly skilled weightlifters - Sadowski, J.; Szyszka, P.; Makaruk, H.; Starzak, M.; Niznikowski, T. (Journal of Human Kinetics, 2024)
Athletes across various sports seek to enhance their power generation and force production by incorporating weightlifting exercises into their training. Therefore, integrating partial weightlifting movements could be sensible due to their simplified execution. Our research aimed to investigate which of four attentional focus strategies (external, internal, holistic, and neutral) would have the greatest impact on performance in terms of power variables for highly experienced weightlifting athletes in a practical training setting. Twelve highly skilled Olympic weightlifters volunteered for the study. They performed 48 single repetitions of the hang power snatch with each of the four attentional focus strategies. Results of the ANOVA did not reveal a significant main effect for maximum velocity, power measurement and displacement. Despite extensive research demonstrating how attentional focus affects performance differently, even among highly skilled populations, the lack of observed effects in our study underscores the challenges of conducting research in applied settings.